CRITICAL THINKING AND PROBLEM-SOLVING SKILLS OF MAKASSAR YOUNG LEARNERS: AN EXPLORATION OF THE ROLES OF LITERACY, GENDER, AND SOCIOECONOMIC STATUS - Suriana Suriana; Anshari Anshari; Mantasiah R.; M. Saleh (Jurnal Gramatika, 2025)
Critical thinking and problem-solving are key 21st-century competencies that determine students’ academic success and life readiness. Although numerous studies have been conducted, most have focused on dispositional aspects and learning strategies, whereas the dimensions of self-confidence and systematic thinking have remained relatively underexplored. This study addresses this gap by examining differences in critical thinking and problem-solving skills based on literacy, gender, socioeconomic status (SES), and maternal educational background. Using a cross-sectional survey design, data were collected from 1,797 junior secondary students in Makassar, Indonesia. Statistical analyses using t-tests and one-way ANOVA were employed to examine mean differences across groups. Results revealed that students with higher reading–writing literacy demonstrated greater self-confidence and more systematic thinking. Female students outperformed males in reflective aspects of critical thinking and problem-solving, whereas SES differences appeared only in the essential systematicity of thinking. No significant differences were found based on maternal education. These findings highlight literacy as the strongest differentiating factor in students’ critical thinking and problem-solving skills. In practice, the study underscores the importance of interdisciplinary, literacy-based instruction to strengthen students’ higher-order thinking skills. Future research should employ longitudinal and mixed-method approaches to explore the mediating role of the cultural environment in shaping young learners’ critical cognition in developing countries.